KEMAMPUAN SISWA KELAS VIII SMP N 4 SOLOK SELATAN MENYIMAK BERITA BERDASARKAN UNSUR 5W+1H - Julnesra, Fina; Laila, Aruna; DN, Upit Yulianti (Pendidikan Bahasa Indonesia, 2013)
The problems in this study discussed the ability of second grade in SMP N 4 Solok Selatan listening to the news by elements 5W +1 H. Listening theory used in learning theory by Tarigan (2008:31). For elements of the  theoretical used 5W +1 H is theory by Suhandang (2004:122 - 123). This research is quantitative descriptive method theory by Arikunto (2006:10). Data was collected using the test. The test used is objective test with four alternatives A, B, C, and D.             This study aimed to describe the ability of second grade in SMP N 4 Solok Selatan find elements 5W +1 H in the news. The data analysis show that the ability to listen what element (What) obtained average ability students 51.04% at nearly qualified enough (HC). The ability to listen to the news element who (Who) obtained average ability students 51.39% at nearly qualified enough (HC). The ability to listen to the news element when (When) obtained average ability students 61.11% at sufficiently qualified (C). The ability to listen to the news element where (Where) obtained average ability students 52.78% at nearly qualified enough (HC). The ability to listen to the news element of why (Why) obtained average ability students 55.56% at sufficiently qualified (C). The ability to listen to the news element of how (How) obtained average ability students 54.17% at nearly qualified enough (HC). From the results of this study concluded that the ability to listen to news of second grade in SMP N 4  Solok Selatan in general was 54.3% at nearly qualified enough (HC) with a value range of 46-55%.